Предмет: Алгебра,
автор: Peacemker
Ответы
Автор ответа:
0
2^(3x)=3
log₂2^(3x)=log₂3
3x*log₂2=log₂3
3x=log₂3
x=(1/3)*log₂3
x=log₂∛3.
log₂2^(3x)=log₂3
3x*log₂2=log₂3
3x=log₂3
x=(1/3)*log₂3
x=log₂∛3.
Автор ответа:
0
log₂2 = 1 , а не 2 или я не прав?
Автор ответа:
0
А где там у меня log₂2 = 2?
Автор ответа:
0
все правильно у тебя тут)
Автор ответа:
0
???? честно говоря, что тут еще можно придумать, понятия не имею...
Приложения:
Похожие вопросы
Предмет: Литература,
автор: tishenko372
Предмет: География,
автор: Duschanov
Предмет: Физика,
автор: forreverrr
Предмет: Алгебра,
автор: kapeglazka